Kepemimpinan Pembelajaran dan Penjaminan Mutu dalam Pembelajaran Biologi: Model Struktural Kinerja Guru pada Konteks Pendidikan Lingkungan - Fahmie Firmansyah; Maharani Maharani; Maya Rahayu; Gigin Ginanjar (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to develop and test a structural model connecting instructional leadership, quality assurance, and biology teacher performance within environmental education. The study uses a quantitative explanatory design with structural equation modeling (SEM) to analyze relationships among variables. Data were gathered from 126 biology teachers at public and private high schools in Cilegon City via a Likert-scale questionnaire. Results indicate that instructional leadership positively and significantly influences mutual assurance of learning, thereby enhancing teacher performance. Mutual assurance partially mediates the relationship between instructional leadership and teacher performance. These findings validate that strong leadership bolsters a sustainable quality assurance system, which is vital to the quality of environmental-based learning. The study offers practical guidance for teacher-training policy development and quality-system enhancement in schools, while inviting further, deeper research into the drivers of environmental education implementation.